Acquired von Willebrand Syndrome: from Pathophysiology to Management - Veyradier, Agnès; Jenkins, Charles S. P.; Fressinaud, Edith; Meyer, Dominique (Thrombosis and Haemostasis, 2000)
Acquired von Willebrand syndrome (AvWS) is a rare and probably underestimated bleeding disorder which mimicks most of the clinical symptoms and laboratory features of hereditary von Willebrand disease (vWD) in patients devoid of both personal and familial history of bleeding diathesis (1). AvWS and congenital vWD both result from a defect in von Willebrand factor (vWF), a large multimeric glycoprotein present in megakaryocytes, platelets, endothelial cells, subendothelium and mainly in plasma (2). vWF is essential to platelet adhesion and aggregation at the site of vascular injury by acting as a bridge between platelet receptors and the collagen of the subendothelium as well as between platelets themselves. vWF binds to both platelet receptors glycoprotein (GP) Ib and GP IIb/IIIa and also to coagulation factor VIII (F.VIII) acting as a stabilizing carrier protein in plasma. The revised classification of hereditary vWD (3) includes three major types: type 1 and type 3 are respectively related to a partial or a total quantitative defect while type 2 (variants including several subtypes) results from a qualitative defect of vWF. Although vWD is well known to be the most common inherited bleeding disorder with a worldwide prevalence of 1 to 2% (1), more than 200 cases of AvWS have been reported since it was described in 1968 (4). It is likely, however, that this number is underestimated since isolated case-reports of AvWS tend to be less published and its diagnosis remains difficult. AvWS is most commonly found together with a variety of concurrent diseases which are mainly clonal hematoproliferative, neoplasia and autoimmune disorders (5-7). The pathophysiological basis of AvWS as well as its response to treatment depend clearly on the associated underlying disease. In this paper, we summarized all the situations where an AvWS may be observed as a function of the anamnestic and clinical data, the pathogenic mechanisms and the laboratory features. Moreover, we propose a therapeutic flow chart based on both data from the literature and personal experience.
Keywords: von Willebrand factor (vWF); hematoproliferative diseases; inhibitor to vWF